Olives and olive oil in health and disease prevention - Preedy, Victor R.; Watson, Ronald R. (Ronald Ross) (Academic Press, 2021)
Olives and Olive Oil in Health and Disease Prevention, Second Edition expands the last releases content and coverage, including new sections on materials in packaging, the Mediterranean diet, metabolic syndrome, diabetic health, generational effects, epigenetics, glycemic control, ketogenic diet, antioxidant effects, the use of olive oil in protection against skin cancer, oleuropein and ERK1/2 MAP-Kinase, oleocanthal and estrogen receptors, and oleocanthal and neurological effects. The book is a valuable resource for food and health researchers, nutritionists, dieticians, pharmacologists, public health scientists, epidemiologists, food technologists, agronomists, analytical chemists, biochemists, biologists, physicians, biotechnologists and students.